Analisis kepuasan pemustaka terhadap layanan perpustakaan dan pusat layanan digital Universitas Muhammadiyah Surakarta selama masa pasca pandemi - Hidayat, Mansur; Utami, Kurnia; Pujianti, Sapta; Nisa, Maria Husnun (FPPTI Jawa Tengah, 2023)
In organizing learning and teaching activities in higher education, the library is one of the main factors in realizing the chess dharma of higher education. The Covid 19 pandemic that has hit the world has slowly but surely experienced a decline, so that all public services have gradually returned to normal, one of which is the Library Service and Digital Service Center of the Muhammadiyah University of Surakarta (UMS). This research uses descriptive quantitative methods to determine the level of user satisfaction. The results of this research as a whole are in the